Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Astrocyte-Derived CXCL10 Induces Neuronal Tau Hyperphosphorylation and Cognitive Impairments in Sepsis - Cuiping Guo; Hang Ruan; Wensheng Li; Yi Liu; Abdoul Razak Yacoubou Mahaman; Qian Guo; You Zhou; Rong Liu; Jianzhi Wang; Chenliang Zhou; Xiaochuan Wang; Shusheng Li (Neuroscience Bulletin, 2026)

Histopathological Insights into Demyelination and Remyelination After Spinal Cord Injury in Non-human Primates - Junhao Liu; Zucheng Huang; Kinon Chen; Rong Li; Zhiping Huang; Junyu Lin; Hui Jiang; Jie Liu; Qingan Zhu (Neuroscience Bulletin, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

The mixture of procyanidins extracted from the lotus seed pod and bilobalide ameliorates scopolamine-induced memory impairment in mice - Li Zhang; Ji-Qu Xu; Shuang Rong; Bi-Jun Xie; Zhi-Da Sun; Yun-Jian Zhang; Lie-Gang Liu (Neuroscience Bulletin, 2009)

Intergeneration CAG expansion in a Wuhan juvenile-onset Huntington disease family - Yuan Liu; Yan Shen; He Li; Hui Wang; Zhen-Rong Yang; Yan Chen; Yan-Ping Tang (Neuroscience Bulletin, 2007)